Novel Fe2O3-doped glass /chitosan scaffolds for bone tissue replacement. Issue 8 (1st June 2018) - El-Meliegy, Emad; Mabrouk, Mostafa; El-Sayed, Sara A.M.; Abd El- Hady, Bothaina M.; Shehata, Mohamed R.; Hosny, Wafaa M.
Abstract: In this study quaternary bioglass system (BG) SiO2 –CaO–Na2 O–P2 O5 doped with Fe2 O3 was prepared by the sol–gel method. Furthermore, 3D scaffolds were designed through blending Fe2 O3 -doped bioglass with chitosan to obtain various compositions of scaffolds by the freeze-drying technique. The thermal behavior, morphological properties, porosity (%), mechanical properties and physicochemical properties of BG and scaffolds were evaluated by DSC/TGA, TEM, SEM, liquid displacement method, universal testing machine, XRD and FTIR. In addition, the in vitro bioactivity of the prepared scaffolds was studied in phosphate buffer saline (PBS) through the determination of PBS ions concentrations, as well as the degradation and the observation of precipitated calcium phosphate layer by SEM coupled with EDX and FTIR behavior. The cell viability of the prepared scaffolds was conducted against Baby Hamster Kidney fibroblasts (BHK-21) cell line. The presence of Fe2 O3 decreased the Tg (from 513 to 390 °C) and the size decreased (from 20.89 to 50.81–13.92–27.87 nm). The scaffolds porosity (%) decreased upon Fe2 O3 doping but the mechanical strength increased. Cell viability results for the designed scaffolds demonstrated acceptable cell viability compared with normal cells. Therefore, the designed scaffolds are promoted as regenerated materials that can be used for bone tissue replacement.